Perceived Physical Literacy of Kindergarten Teachers in Urban and Rural Areas - Gita Febria Friskawati (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
This study aimed to reveal physical literacy perception differences among early childhood teachers at the kindergarten level of education. The survey research was conducted on 98 kindergarten teachers in West Java who were willing to be involved in this research selected through convenience sampling by filling out an online instrument. Perceived Physical Literacy Scale for Physical Education Teachers (PPLI) was used as the instrument to collect data. The research data were calculated using SPSS 20 employing the ANOVA test. The study's results revealed that physical literacy perception differences were apparent in early childhood education teachers in urban and rural areas, especially in different age and teaching experience groups. The relatively young teachers had diverse perceptions of physical literacy. In contrast, early childhood education teachers in rural schools had the same perception of physical literacy due to the lack of information about the novelty of physical literacy. The findings revealed that the physical literacy perception among early childhood education teachers in urban and rural areas had not been evenly distributed. Therefore, promoting the importance of physical literacy integrated into the learning process, especially in early childhood education, needs to be well socialized through government policies in urban and rural areas.